Surface Functionalization of Hydroxyapatite Scaffolds with MgAlEu‐LDH Nanosheets for High‐Performance Bone Regeneration - Guanyun Wang; Zehui Lv; Tao Wang; Tingting Hu; Yixin Bian; Yu Yang; Ruizheng Liang; Chaoliang Tan; Xisheng Weng (Advanced Science, 2023)
Abstract Although artificial bone repair scaffolds, such as titanium alloy, bioactive glass, and hydroxyapatite (HAp), have been widely used for treatment of large‐size bone defects or serious bone destruction, they normally exhibit unsatisfied bone repair efficiency because of their weak osteogenic and angiogenesis performance as well as poor cell crawling and adhesion properties. Herein, the surface functionalization of MgAlEu‐layered double hydroxide (MAE‐LDH) nanosheets on porous HAp scaffolds is reported as a simple and effective strategy to prepare HAp/MAE‐LDH scaffolds for enhanced bone regeneration. The surface functionalization of MAE‐LDHs on the porous HAp scaffold can significantly improve its surface roughness, specific surface, and hydrophilicity, thus effectively boosting the cells adhesion and osteogenic differentiation. Importantly, the MAE‐LDHs grown on HAp scaffolds enable the sustained release of Mg2+ and Eu3+ ions for efficient bone repair and vascular regeneration. In vitro experiments suggest that the HAp/MAE‐LDH scaffold presents much enhanced osteogenesis and angiogenesis properties in comparison with the pristine HAp scaffold. In vivo assays further reveal that the new bone mass and mineral density of HAp/MAE‐LDH scaffold increased by 3.18‐ and 2.21‐fold, respectively, than that of pristine HAp scaffold. The transcriptome sequencing analysis reveals that the HAp/MAE‐LDH scaffold can activate the Wnt/β‐catenin signaling pathway to promote the osteogenic and angiogenic abilities.